Manifestation of Gender Injustice in Households Amidst the Pandemic - Kusniati, Endang (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
The marriage bond was fostered for the realization of sakinah family. However, not all Households life runs harmoniously. When the COVID-19 pandemic hit, it not only disrupted the stability of the country, health, but also disrupted the stability of the family. Divorce phenomena and factors that occur in amidst the pandemic arise due to a crisis of trust, disputes, domestic violence, rooted in the economy. Apart from that, there are other factors; age of marriage, age of the couple (person), economic independence and education. The total number of cases that went to the Sungailiat Class 1B Religious Court 2020; 219 divorce cases and 607 divorce cases, total of 826 cases. While divorces have been declared terminated by the Religious Courts as many as 203 divorced divorces and 538 lawsuits, a total of 741 cases. This research aims to determine the phenomena of divorce in the Class 1B Sungailiat Religious Court 2020, to determine the factors that cause divorce in amidst the pandemic, to determine the manifestation of gender injustice in household and to find out how to build a sakinah family. The theory used; Gender Differences (Mansour Fakih). This research is included in non-statistical (qualitative) field research. While the data obtained are described according to the facts from primary data and secondary data, by using semi structure interview and documentation